2005
DOI: 10.1128/iai.73.9.6157-6164.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of Toll-Like Receptor 4 in the Proinflammatory Response to Vibrio cholerae O1 El Tor Strains Deficient in Production of Cholera Toxin and Accessory Toxins

Abstract: Following intranasal inoculation, Vibrio cholerae KFV101 (⌬ctxAB ⌬hapA ⌬hlyA ⌬rtxA) colonizes and stimulates tumor necrosis factor alpha and interleukin 1␤ (IL-1␤) in mice, similar to what occurs with isogenic strain P4 (⌬ctxAB), but is less virulent and stimulates reduced levels of IL-6, demonstrating a role for accessory toxins in pathogenesis. Morbidity is enhanced in C3H/HeJ mice, indicating that Toll-like receptor 4 is important for infection containment.Vibrio cholerae is a gram-negative pathogen that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…Toll-like receptor 4 (TLR4) can be activated by V. cholerae LPS in vitro (18). Also, after nasal infection with V. cholerae lacking proinflammatory toxins CTX, RtxA, and HlyA, morbidity was greater for mice lacking TLR4 expression, suggesting a role for TLR4-mediated inflammation in bacterial containment in the absence of other sources of inflammation (23). Using human epithelial cell lines, TLR5 was implicated in V. cholerae flagellin-induced inflammation (14,15), although the sheath covering the V. cholerae flagellum reduces the potency of TLR5 signaling (24).…”
mentioning
confidence: 99%
“…Toll-like receptor 4 (TLR4) can be activated by V. cholerae LPS in vitro (18). Also, after nasal infection with V. cholerae lacking proinflammatory toxins CTX, RtxA, and HlyA, morbidity was greater for mice lacking TLR4 expression, suggesting a role for TLR4-mediated inflammation in bacterial containment in the absence of other sources of inflammation (23). Using human epithelial cell lines, TLR5 was implicated in V. cholerae flagellin-induced inflammation (14,15), although the sheath covering the V. cholerae flagellum reduces the potency of TLR5 signaling (24).…”
mentioning
confidence: 99%
“…In an infant rabbit model of infection, this diarrhea has been specifically linked to expression of flagellin that may be functioning by increasing inflammatory signaling through TLR5 (20,46,47). Studies using lung infection in mice have also linked proinflammatory signaling from CT-negative strains to LPS-dependent signaling through TLR4 (18), whereas lipoprotein has been shown in vitro to stimulate inflammation via TLR1/TLR2 (16,25). Thus, the prevailing models suggest that bacterial factors induce a proinflammatory response that then causes significant diarrhea, resulting in either serious clinical symptoms during natural infection with nontoxigenic strains or reactogenic symptoms in vaccine studies.…”
mentioning
confidence: 99%
“…However, little is known about their role in vivo as no overt defects in mutants in relevant animal models have been observed. A role for accessory toxins in pathogenesis in a pulmonary infection model was indicated previously (12,16); however, as the lung is not the natural site of infection, the relevance of these studies was questioned. In this study, we established a new model for the intestinal infection of 4-to 6-week-old C57BL/6 mice with V. cholerae.…”
mentioning
confidence: 99%
“…Indeed, a strain in which the genes for CT and all three accessory toxins were deleted was avirulent after intranasal infection, and the colonizing bacteria were cleared from the lung (12). Yet this multitoxin-deficient strain stimulated the innate immune response in a classical fashion through multiple pathways both dependent upon and independent of Toll-like receptor 4 (16). These results suggested that accessory toxins function coordinately to enable the bacteria to evade the host immune response and prevent clearance of the colonizing bacteria during the early stages of infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation